An experimental test of the Anscombe-Aumann Monotonicity axiom - Florian H. Schneider; Martin Schonger (University of Zurich, Department of Economics, 2017)
Most models of ambiguity aversion satisfy Anscombe-Aumann's Monotonicity axiom. Monotonicity imposes separability of preferences across events that occur with unknown probability. We construct a test of Monotonicity by modifying the Allais paradox to a setting with both subjective and objective uncertainty. Two experimental studies are conducted: while study 1 uses U.S. online workers and a natural source of ambiguity, study 2 employs European students and an Ellsberg urn. In both studies, modal behavior violates Monotonicity in a specific, intuitive way. Overall, our data suggest that violations of Monotonicity are as prevalent as violations of von Neumann-Morgenstern's Independence axiom.
Keywords: D81; 330; Ambiguity aversion; monotonicity; Anscombe-Aumann; Allais paradox; experiments